Casual Sex Among Emerging Adults: A New Measure of Casual Sex and its Relation to Well-Being - Borisevich, Severina (Université d'Ottawa / University of Ottawa, 2023)
Casual sexual relationships and experiences (CSREs) are a common phenomenon experienced by the majority of emerging adults attending college and university. Despite researchers' increased interest towards the topic of casual sex in recent years, there is a lack of validated psychometric measures that operationalize different types of CSREs and an absence of uniformity in the definitions of casual sex. Few studies distinguish clearly between different types of CSREs and few studies include a balanced approach when considering well-being outcomes (i.e., negative and positive markers). The first study of this dissertation aimed to bridge the research gap through the development and validation of the Casual Sex Experiences Scale (CASEX), which measures frequency of four types of CSREs (one-night stands, booty calls, fuck buddies, and friends with benefits). The CASEX's validity (factorial, convergent, divergent) and reliability (internal consistency) were tested in two independent samples. The results indicated that the CASEX can indeed measure the four aforementioned types of CSREs. In the second study, we examined how those four types of CSREs were related to well-being in consensual sexual interactions in a cross-sectional study. We included positive and negative markers of wellbeing. Moreover, we tested whether the relation between CSREs and well-being was moderated by sociosexual attitudes. We derived hypotheses from the theory of cognitive dissonance related to the potential moderating effect of sociosexual attitudes. Participants reported a coexistence of negative and positive well-being outcomes related to CSREs (e.g., positive and negative emotions during and following casual sex). In most cases, sociosexual attitudes did not moderate the relationships between CSREs and well-being outcomes. However, a notable exception was that sociosexual attitudes moderated relationships between CSREs and emotions experienced during and following casual sex, which was expected from the theory of cognitive dissonance. As hypothesized, the relationship between casual sex and negative emotions during and following casual sex was stronger in those participants with less sociosexual attitudes. Nonetheless, some results refuted our hypotheses, for instance, some relationships between casual sex and positive emotions during and following casual sex were stronger in those participants with less sociosexual attitudes. In other words, casual sex seemed to have been less of an emotional experience (positive or negative) in those with more sociosexual attitudes. Overall, this dissertation provides initial evidence in favour of the validity and reliability of the CASEX, which can enable to understand more nuanced relationships between experiences of casual sex and well-being among emerging adults. Findings deepened the understanding of the role of sociosexual attitudes in the relations between different types of CSREs and well-being markers.
Keywords: emerging adults; casual sex; well-being